1961
DOI: 10.1107/s0365110x61000553
|View full text |Cite
|
Sign up to set email alerts
|

Studies of some carbon compounds of the transition metals. II. The structure of MeC: CMe.H2F2(CO)8

Abstract: The structure of the complex MeCi CMe.H2Fe~(CO)8, isolated from the reaction of but-2-yne with alkaline solutions of iron hydrocarbonyl, has been determined by three-dimensional Fourier methods and refined by least-squares methods. The compound crystallizes in the monoclinic system, space group P2t/c, with four molecules in a unit cell of dimensions a=12.26, b=7.47, c=15-7 A, fl=97.5 °.The structure exhibits a number of novel features which include (i) a four-carbon chain chelated on to one of the iron atoms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

1962
1962
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(18 citation statements)
references
References 0 publications
3
15
0
Order By: Relevance
“…Various ferroles have been obtained by reacting acetylenes and iron carbonyl in water [21] or in alkaline solutions [22] and by refluxing a solution of Fe 3 (CO) 12 and alkynes in hydrocarbon solvents [23]. Decomplexation reactions of nickel maleoyl complexes [Ni(bpy){C 2 R 2 (CO) 2 }] [24] and of some acyloxy ferrole complexes [25] have led to isolation of cyclobutendiones, C 2 R 2 (CO) 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Various ferroles have been obtained by reacting acetylenes and iron carbonyl in water [21] or in alkaline solutions [22] and by refluxing a solution of Fe 3 (CO) 12 and alkynes in hydrocarbon solvents [23]. Decomplexation reactions of nickel maleoyl complexes [Ni(bpy){C 2 R 2 (CO) 2 }] [24] and of some acyloxy ferrole complexes [25] have led to isolation of cyclobutendiones, C 2 R 2 (CO) 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The structure of the but-2-yne complex, as determined by Hock and Mills (136,137), is shown diagrammati-forms a five-membered ring with two CO groups and a Fe(CO)3 group, and this diene system is coordinated to another Fe(CO)3 group. By donation of an unshared pair of electrons from the latter iron atom to the former, each achieves an inert gas configuration.…”
Section: Metal Carbonyl-acetylene Reactionsmentioning
confidence: 92%
“…The first structurally characterized SBCO ligand was reported in 1961 by Hock and Mills, 29 who found that one of the putatively terminal CO ligands in diiron complex 1 (Fig. 2a) was anomalously "bent" (∠(Fe-C-O) = 168°) despite the Fe II ⋯CO distance (2.484 Å) being "clearly too long for any simple interaction".…”
Section: A Brief History Of Sbco Structuresmentioning
confidence: 98%